Development of omni directional mobile robot navigation system using RFID - Rashid, Muhammad Mahbubur (s.n, 2012)
A present a modular navigation technique in relation with the signal from RFID tags, and RFID reader. We will come out with the simplest circuit and micro-controller to navigate the identification number on RFID tags. The main idea is to test the ability of mobile robot to navigate the location in indoor environments. The RFID reader is mounted on the mobile robot to communicate with the RFID tags to determine robot's position while the RFID tags are attached at different location. The position of mobile robot is determined according to the location of FRID tag. The actuator will be moved according to the angle between the robot's current position and target tag